Outcome of chair-based exercise on physical performance and quality of life of older women : a preliminary study in Kuala Lumpur, Malaysia - Razaob NA; Ab. Rahman NNA; Nor Azlin Mohd Nordin; EE, FSY; Lee, JH; Doherty P (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Chair based exercise (CBE) is an exercise alternative for older adults in ensuring safety during exercise. Its evidence of effectiveness is currently limited to frail older adults or those with acute medical conditions or terminal illnesses. Given higher exercise difficulty level, CBE could benefit healthier older adults and can be an exercise option for this population. This study was designed to evaluate the outcome of a CBE on physical performance and quality of life in community-dwelling older women in Malaysia. A total of 18 older women (mean age 66.78 + 4.60 years) completed CBE at twice-per-week for eight weeks. Exercise outcomes were measured using six minutes’ walk test (6MWT), five times sit to stand test (FTSTS) and hand-held dynamometer for physical endurance, functional lower limb strength and grip strength, respectively. A Malay version of the World Health Organization quality of life scale (WHOQOL-BREFMalay) was used to measure the health status and QOL of the participants. All data were analysed with the use of inferential statistics, with significance level set at p<0.05. The mean distance walked in 6MWT improved after CBE (p<0.001), indicating greater physical endurance. Significant improvements were also found in the overall QOL, and in the general health, physical health, psychological and environment domains of the WHOQOL-BREFMalay (p<0.05). However, no significant changes were demonstrated in the FTSTS and grip strength following the exercise. CBE enhances physical endurance and quality of life among older women in the selected community and can be an exercise option for this population.